TO EVALUATE EFFICACY OF ASTHISHRUNKHALA (CISSUS QUADRANGULARIS) ON ACCELERATION OF BONE HEALING IN FRACTURED BONE - Kharik Amol; Morade Swati; Surse Yogesh; Dehankar Manisha (International Journal of Ayurveda and Pharma Research, 2019)
The healing of a fracture is one of the most remarkable of all the repair processes in the body since results not in a scar but in the actual reconstitution of the injured tissue in something very like its original form. It is not to be expected therefore that the mechanisms controlling such a process will be easily elucidated and indeed they involve problems of cellular homeostasis which are among the most fundamental in biology. If it is not quite thou cunning’st pattern of excelling nature, then it is something quite close to it and a great deal of that pattern. Present study shows experimental evaluation of effect of Asthishrunkhala (Cissus quadrangularis) on bone healing in fractured bone by histo-pathological study. During study concerned literature was reviewed critically. The study was divided into phytochemical, pharmacological and histopathological study. Drug was identified and authenticated from authorized institute and phytochemical screening done after successive extraction of extract. Two groups were made. First Group A (Treatment group) was further divided into six subgroups containing five animals each received extract of Cissus quadrangularis 500mg/kg body weight, Group B is control group. After completing the study it was observed that mature bone or bone repair process seen weakly at 2nd – 3rd week proving the acceleration of bone healing process with gradual re-modeling. Statistical analysis shows that histopathological study in group A found to be highly significant p<0.001 from 4th week onwards. Overall the bone healing process shows 10% faster healing period in group A than group B.